The Impact of Sports Participation on College Students’ Learning Outcomes: A Mixed Methods Study based on Multiple Campuses - Liu, Tianyue; Taresh, Sahar (Journal of Ecohumanism, 2024)
Plato said: In order for humans to have a successful life, God provides two channels-education and sports. We are increasingly seeing that these two channels are complementary and indispensable. Modern neuroscience research shows that sports can have beneficial effects on brain structure and function, epigenetic regulation of brain tissue, cerebral cortex activity patterns and learning-related psychological factors, thereby improving students’ cognitive abilities and academic performance. This study aims to explore the multifaceted effects of sports participation on college students’ learning outcomes. A mixed research method was used to collect data in three different types of universities, including a questionnaire survey of 500 students and in-depth interviews with 20 students and 10 faculty members. Quantitative analysis showed that moderate sports participation was significantly related to better academic performance, higher mental health and stronger time management skills. However, excessive participation in physical activities may have a negative impact on study time. Qualitative data further revealed how sport participation enhanced students’ self-confidence, teamwork and stress management skills. The study also found that the impact of sports participation varies depending on students’ personal backgrounds and the characteristics of their universities. Based on the research results, this article puts forward practical suggestions to promote the balanced development of college students, providing a basis for higher education institutions to formulate relevant policies.